(untitled) (Scientific journal of the Fergana State University, 2023)
In this article the activity of mutual household which functioning in the sector of agriculture of Uzbekistan in the period of Independence are analysed. Also, the problems of mutual households` as well as matters connected with applying sanitation regarding unprofitable mutual household and their elimination are considered.